Strategi Prioritas Pengembangan Usaha Penggemukan Sapi Potong di Kota Tanjungpinang dengan Menggunakan Metode Analytical Hierarchy Process (AHP) - Eko Sutrisno; Kusmiati Kusmiati; Muhammad Alfatih (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
The increasing demand for beef in Tanjungpinang is reflected in the market opportunity. However, local beef production does not meet market demand. Thus, beef supplies are expected from outside the region. This dependency results from the area's minimal development and efficiency of beef cattle farming. The potential in the livestock sector is not fully utilized, thus creating opportunities to increase regional production and reduce dependence on external supplies. This research was conducted to develop a priority strategy for beef cattle development in Tanjungpinang. This study was conducted in Tanjungpinang using quantitative analysis methods. Purposive sampling is used as a technique. The subjects in this study included a population of farmers who have consistently run beef cattle farming businesses for the past 5 years. Referring to the predetermined criteria, the sample in this study consisted of 44 farmers. SWOT and Analytical Hierarchy Process (AHP) methods were used in data analysis. The priority strategies for developing the beef cattle fattening agribusiness in Tanjungpinang include establishing partnerships with the government and private sector, developing agricultural and livestock areas in potential subdistricts through modernization, implementing agribusiness livestock field schools and training on producing high-nutrient livestock feed, facilitating and socializing the KUR (Kredit Usaha Rakyat) program, increasing the beef cattle population, creating alternative feed from agricultural waste, introducing agricultural feed processing technologies, and superior cattle breeds tailored to local conditions, Improving the effectiveness of business management and optimizing the role and function of livestock groups and reapplying modern livestock practices from major production centers.